Influencia de la gestión de capacitación en el desempeño laboral de los docentes de la facultad de ciencias sociales de la Universidad Nacional de Trujillo, 2010 - Sánchez Correa, Yesenia (2011)
There was studied the influence of the management of training in the labor educational performance of the Facultad de Ciencias Sociales of the Universidad Nacional de Trujillo, year 2010. In this study of type descriptive - correlacional, one worked with the universe of the population, constituted by 37 teachers of the Facultad de Ciencias Sociales, regular and present in the date of the compilation of information; also there decided a students' representative sample, integrated by 222 pupils of the different Schools Academic professionals of the Facultad. The methods were in use inductively - deductively, analytical synthetically and statistically, as well as the technologies of review of files, observation, interview and survey. The obtained results show that the level of management of the training is qualified in major percentage by a low level (62 %) and in minor percentage by a regular level (38 %); and as for the level of educational performance, this one is qualified in major percentage (78 %) by a high level, and in minor percentage (22 %) by an average level. Therefore, it is possible to demonstrate the influence of the Management of Training in the Labor Performance, by means of a significant relation between both variables (according to the teacher with a level of significancia p = 0.001, according to head of department and pupils with a level of significancia p = 0.000).